Analisis Kecepatan Tanah Maksimum di Daerah Akibat Gempa Bumi Lombok di Daerah Pengamatan Labuan Bajo, Waingapu dan Maumere Nusa Tenggara Timur 05 Agustus Tahun 2018 - pangge, claudius eswinsky; Subagiada, Kadek; Djayus, Djayus (GEOSAINS KUTAI BASIN, 2022)
The ground motion velocity of an earthquake can cause material damage and loss. The purpose of this study was to analyze the maximum ground motion velocity caused by an earthquake. The data used were secondary data for earthquakes that occurred in the Lombok area of ​​West Nusa Tenggara on August 5 2018 at 06:46:37 p.m indonesian middle time zone, with the observation areas of Labuan Bajo (East Nusa Tenggara), Waingapu (East Nusa Tenggara), and Maumere (Nusa Tenggara). East Southeast). The data of this research include the coordinates of the earthquake area, the coordinates of the observation stations, the magnitude of the earthquake, and the acceleration value of ground motion as a comparison. Those data furthermore calculated the epicenter distance, the earthquake intensity value, and the ground motion velocity value was analyzed then compared with the ground acceleration value after which it was connected to the MMI scale. The results showed that the ground velocity value of the Labuan Bajo observation area was 3.66 cm / s, Waingapu 0.99 cm / s and the Maumere area 0.98 cm / s with a damage effect according to the MMI category II scale.